Research on the impact of basic psychological needs satisfaction on career adaptability of Chinese college students - Xu, Min; Lu, Haidong; Guo, Qi (Frontiers in Psychology, 2023)
Introduction With social changes, the realization of smooth and satisfactory employment of college students is an issue that requires deep thought. Basic psychological needs satisfaction play an important role as a guiding factor that affects students’ career adaptability. This study aims to explore the relationship and mechanism between the satisfaction of students’ basic psychological needs satisfaction and their career adaptability. Methods A survey is conducted among students from six different universities across the country, using the Basic Psychological Needs Satisfaction Scale, the Career Adaptability Scale, the Career Decision Self-Efficacy Scale, and the Career Outcome Expectations Scale. Results The satisfaction of basic psychological needs, career decision self-efficacy, and career outcome expectations are all significantly positively correlated with career adaptability.Career decision self-efficacy plays a partial mediating role between basic psychological needs satisfaction and career adaptability among college students. The moderated mediation model found that career outcome expectations play a regulatory role in the effect of career decision self-efficacy on career adaptability. Discussion College students’ basic psychological need satisfaction can positively predict career adaptability directly and indirectly affect career adaptability through career decision self-efficacy, and career outcome expectations have a moderating role between career decision self-efficacy and career adaptability.